Pengaruh Model Pembelajaran Autentik terhadap Keterampilan Berpikir Kritis Siswa SMA - Angelina, Natasya Mia; Suciati, Rizkia; Safahi, Luthpi; Astuti, Yuni (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Critical thinking skills are one of the 21st century skills that students must have. Students can master these skills so they can develop life skills and soft skills. Critical thinking skills can be developed by connecting learning material with real experiences in everyday life, thereby encouraging students to analyze. This research aims to determine the effect of authentic learning models on high school students’ critical thinking skills. The research method used was quasi-experiment, post-test only control design with 1 experimental class and 1 control class. The research instrument is a written test in the form of a description totaling 13 questions. The results of the research showed that the hypothesis test obtained a tcount value of 5.676 > ttable of 1.997 so that the critical thinking skills data in the experimental class was significantly different from the critical thinking skills in the control class. This research can be concluded that the authentic learning model influences high school students’ critical thinking skills.